Int. J. Adv. Res. Biol. Sci. 2017
DOI: 10.22192/ijarbs.2017.04.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Parotid and Mandibular Salivary Glands Segmentation Of The One Humped Dromedary Camel (Camelus dromedarius)

Abstract: The present study provides detailed anatomical description of the parotid and mandibular salivary glands of the one humped camel with their segmentation based on arterial blood supply and salivary ducts; to facilitate partial removal of the pathologic gland. The shape, position, relations and blood supply of both salivary glands with their ducts were studied on six cadaveric heads. The mandibular and parotid ducts were injected with Urographin® as contrast medium; through inserting the catheter into their open… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…The present study revealed that each parotid salivary gland had three angles, including pre-auricular, postauricular, and masseteric angle (ventral angle), which is in accordance to a previous report in the dog (Gaber et al 2020), but in contrast to reports in cattle (Al-Sadi 2013) and camels (Rezk and Shaker 2017), where five processes were recorded. According to Dyce et al (2010) in dogs, the masseteric angle formed the apex of the gland; it was a thin elongated lobe, extending between the caudal border of the masseter and rostral border of the mandibular salivary gland.…”
Section: Gross Anatomical Featuressupporting
confidence: 93%
See 3 more Smart Citations
“…The present study revealed that each parotid salivary gland had three angles, including pre-auricular, postauricular, and masseteric angle (ventral angle), which is in accordance to a previous report in the dog (Gaber et al 2020), but in contrast to reports in cattle (Al-Sadi 2013) and camels (Rezk and Shaker 2017), where five processes were recorded. According to Dyce et al (2010) in dogs, the masseteric angle formed the apex of the gland; it was a thin elongated lobe, extending between the caudal border of the masseter and rostral border of the mandibular salivary gland.…”
Section: Gross Anatomical Featuressupporting
confidence: 93%
“…Our results revealed that the dorsal border of the parotid salivary gland in the dog was notched by the auricular cartilage, which is in line with the findings of Dyce et al (2010) in dogs, Pereira and Faria Júnior (2018) in crab-eating foxes and Maher et al (2020) in donkeys. On the other hand, in red fox, the parotid gland was thicker than in dog, while dorsal border of the gland was not notched, as has been observed by Al-Sadi (2013) in cattle and Rezk and Shaker (2017) in camels.…”
Section: Gross Anatomical Featuresmentioning
confidence: 60%
See 2 more Smart Citations
“…These observations are noticed grossly in small ruminants (El‐hagri, 1967; Habel, 1975; Nickel et al, 1979) and large ruminants (Ahmed, 1988). The caruncles are roughly quadrilateral in shape in Bakerwali goat (Sarma et al, 2012), and appeared as slightly raised circular area in camel (Rezk & Shaker, 2017; Smuts & Bezuidenhout, 1987). Sarma et al (1995) reported that the sublingual caruncles are wide, hard papillae with serrated border in yak.…”
Section: Discussionmentioning
confidence: 99%